X-Tream dosimetry of highly brilliant X-ray microbeams in the MRT hutch of the Australian Synchrotron. (November 2017) - Fournier, Pauline; Cornelius, Iwan; Dipuglia, Andrew; Cameron, Matthew; Davis, Jeremy A.; Cullen, Ashley; Petasecca, Marco; Rosenfeld, Anatoly B.; Bräuer-Krisch, Elke; Häusermann, Daniel; Stevenson, Andrew W.; Perevertaylo, Vladimir; et al.
Abstract: The X-Tream dosimetry system developed at the Centre for Medical Radiation Physics (University of Wollongong, Australia) utilises a high resolution silicon Single Strip Detector to characterise synchrotron radiation microbeams for the purpose of Quality Assurance of Microbeam Radiation Therapy. Firstly, a comparison of the Silicon Strip Detector performance with respect to a conventional PinPoint Ionisation Chamber for broad beams and microbeams is given. These results are then extended to characterise the horizontal microbeam radiation field available in the high flux experimental hutch of the Imaging and Medical BeamLine at the Australian Synchrotron. The Silicon Strip Detector measured depth dose curve of the broad beam agrees very well with the PinPoint Ionisation Chamber measurements between 10 and 50 mm depth in water. Significant deviations from the PinPoint Ionisation Chamber response are observed with increasing depth. Microbeam profiles measured by the Silicon Strip Detector are well resolved but clearly affected by misalignment of the Silicon Strip Detector with respect to the microbeams. Future beamline technical improvements will alleviate this issue. Highlights: The Silicon Strip Detector is a valid tool for use in Microbeam Radiation Therapy. Successful measurement of Full Width Half Maximum achieved. Successful measurement of Peak to Valley Dose Ratio achieved. Over response of measurements observed due to alignment issues and device geometry. A new Silicon Strip Detector has been developed with improved spatial resolution.